Prioridade política e capacidade burocrática: a implementação do PAC-Urbanização de Assentamentos Precários - Silva, Fernanda Lima e (2019)
This thesis aims to explore the local factors that explain the different results obtained by municipal governments in the implementation of the same urban policy shared with the federal government: slum upgrading initiatives within PAC. Based on an analytical framework built from the literature on state capacity and implementation of public policies, it analyzes different local aspects, such as the priority of slum upgrading in the municipal agenda, technical and political abilities of municipal high-level bureaucrats to implement the program and to align different actors involved in the policy-making and, to a lesser extent, the spatial characteristics of cities and slums. Methodologically, the thesis was structured from a mixed research method, integrating statistical analyzes with the detailed investigation of the selected case studies: the municipalities of Campo Grande (MS), Santo André (SP), São Bernardo do Campo (SP) and Pelotas (RS). The results of the research indicate, firstly, that municipal bureaucratic or institutional capacity was an important precondition, but it did not mean high capacity for implementation. The prioritization of slum upgrading on the local political agenda proved to be a more relevant explanatory factor, which resulted in the additional allocation of resources - financial, informational and human -, 'activating' and strengthening bureaucratic capacity and anchoring successful implementation efforts. Finally, the research points to the unstable nature of the implementation capacity building process, which is affected by variations in the local and national political context; a process that becomes more expressive in areas of politics such as the one emphasized here, whose trajectory is marked by the programmatic inconstancy and by the inexistence of an effective system of public policies.